GENDER RELATIONSHIP, WORK PERIOD, JOB SATISFACTION, COMMITMENT AND ORGANIZATIONAL CULTURE WITH ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) AT ANWAR MEDIKA SIDOARJO RSU - Anggoro Susanto; Achmad Yudi Arifiyanto; Nyoman Anita Damayanti; Nungky Taniasari; Budhi Setianto (UNUSA Press, 2022)
The success of an organization depends on human resource management. OCB is a voluntary action in creativity and innovation designed to improve the performance of a person or organization with diligence and enthusiasm, take more responsibility and encourage others to do the same. One of the challenges that must be faced is the low OCB. Some incidents that reflect low OCB behavior include: difficulty finding a replacement when a co-worker is absent, a lack of commitment to doing work outside of routine work and a strong sense of caring. Therefore, an analysis is needed to determine the relationship between gender, tenure, job satisfaction, commitment, organizational culture and OCB at Anwar Medika Hospital, Sidoarjo. To determine the relationship between gender, tenure, job satisfaction, commitment, and organizational culture with Organizational Citizenship Behavior (OCB) at Anwar Medika Hospital, Sidoarjo. The research method used is descriptive quantitative. There are two variables in this study, namely the independent variable and the dependent variable. The independent variables include: gender (X1), tenure (X2), job satisfaction (X3), commitment (X4), organizational culture (X5). The dependent variable in this study is Organizational Citizenship Behavior (Y). There are 3 data analysis techniques in this study, namely: Pearson validity test, Cronbach alpha reliability test, and chi-square test. Based on the results of measuring the OCB level of the employees of Anwar Medika Hospital on January 1, 2021, it was found that 51% of employees had high OCB and 49% had low OCB. The Pearson validity test shows r count> r tabel (0.1030), and a significance value <0.05. Cronbach alpha test> 0.06. There is no relationship between gender and OCB (p = 0.07), there is a relationship between tenure and OCB (p = 0.01), there is a relationship between job satisfaction and OCB (p = 0.00) There is no relationship between gender and OCB. There is a relationship between tenure and OCB. There is a relationship between job satisfaction and OCB. There is a relationship between commitment and OCB. There is a relationship between organizational culture and OCB.